A Contradiction of the Existence of English in Rural and Urban Pesantren in Indonesia - Azami, Mochamad Imron (IJET (Indonesian Journal of English Teaching), 2021)
Pesantren emphasizes the learning on religious knowledge, based on the classical textbook given to Santri (student). Nowadays, pesantren shifts its tradition by providing English program. This shifting occurs as the effort of pesantren to face the challenges of modernization and to fulfill the demands of society. This paper discussed the comparative study of English program implementation history in rural and urban pesantren, the reasons for establishing English program, and santries’(student) response towards English program in pesantren. The result showed that the existence of English program in pesantren, both in rural and urban area, was because the demand of the society. In rural pesantren, the reason why they provided English because they wanted to develop the society surrounded pesantren which are Indonesian Migrant Worker (Tenaga Kerja Indonesia). While in urban area, they provided English program because they were focusing on the development of santries themselves to prepare for the global community.